Association Between Obstructive Sleep Apnea, Its Treatment, and Alzheimer's Disease: Systematic Mini-Review - Kuo, Chih-Yun; Hsiao, Hung-Ta; Lo, Ing-Hsien; Nikolai, Tomas (Frontiers in Aging Neuroscience, 2021)
The obstructive sleep apnea (OSA) and Alzheimer`s disease (AD) are common in elderly population. Obstructive sleep apnea that may cause significant changes in the cerebrospinal fluid β-amyloid, and T-tau and/or P-tau protein levels, is often identified as a risk factor for development of AD. Although the underlying mechanisms of AD are still not fully understood, hypothesis associating OSA with AD has been already proposed. In this systematic mini-review, we first discuss the recent findings supporting association of OSA with an increased risk of AD and, then, provide evidences suggesting the positive effect of OSA treatment on the reduced risk of AD.